Experimental Validation of Upward Electrospinning Process. (25th December 2011) - Abdel-Hady, Faissal; Alzahrany, Abdulrahim; Hamed, Mostafa
Abstract : An experimental investigation has been carried out to validate the concept of a new upward electrospinning process in producing polymer nanofibres. The role of gravitational force in this concept is reversed from the conventional downward electrospinning. This inversion results in more stretching of the fibre, less bead formation, and jet stability. An experimental setup is built inside a vacuum chamber in order to eliminate the ambient effects. The effect of various parameters such as applied voltage, needle-collector distance, solution concentration, flow rate, and needle size, on average fibre diameter and beads formation, was investigated using scanning electron microscopy (SEM).